Food Security and Psychological Distress among the Elderly in India. Issue 2 (December 2022) - Gogoi, Pallabi; Hazarika, Bhabesh
Food insecurity affects nutrition, physical health and consequently one's psychological well-being. Using a nationally representative longitudinal cohort of 29, 308 Indian elderly people (aged 60+ years), this article examines the relationship between food insecurity and psychological distress. Self-reported emotional status experienced over the week before data collection was considered to construct psychological distress at the individual level. Based on the results of logistic regression, controlling for several demographic and socioeconomic factors, a strong relationship was observed between food insecurity and psychological distress among the Indian elderly. This relationship is moderately higher in females than in males when accounting for demographic and socioeconomic confounders. These findings have important policy implications urging intervention to enhance food security in the elderly at risk and to improve their physical and psychological health.